1971
DOI: 10.1002/ar.1091710403
|View full text |Cite
|
Sign up to set email alerts
|

Structure of mammalian portal vein: Postnatal establishment of two mutually perpendicular medial muscle zones in the rat

Abstract: In all mammalian species examined thus far, the media of the adult mammalian portal vein consists of two mutually perpendicular smooth muscle zones separated by a fibrous layer. The cells of the muscle zone nearest the intima are arranged circumferentially and resemble smooth muscle of other vessels; the muscle cells of the thicker, vascularized outer zone are longitudinal and contain mitochondria and pinocytotic vesicles in great abundance, suggesting relatively high metabolic activity. The adult configuratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…The rat portal vein provides a more physiologically relevant system to study the mechanisms of phenotypic modulation compared to a cultured cell system, where a fully differentiated VSM phenotype is not possible. In the neonatal portal vein (rat and human) smooth muscle cells are in an undifferentiated, proliferating (hyperplastic) state and resemble myoblasts [22]. At 2 -4 days the neonatal portal vein is contractile although has lower levels of smooth muscle-specific proteins [15] and expresses known markers of proliferation [19] as previously demonstrated by our group.…”
Section: Discussionsupporting
confidence: 70%
“…The rat portal vein provides a more physiologically relevant system to study the mechanisms of phenotypic modulation compared to a cultured cell system, where a fully differentiated VSM phenotype is not possible. In the neonatal portal vein (rat and human) smooth muscle cells are in an undifferentiated, proliferating (hyperplastic) state and resemble myoblasts [22]. At 2 -4 days the neonatal portal vein is contractile although has lower levels of smooth muscle-specific proteins [15] and expresses known markers of proliferation [19] as previously demonstrated by our group.…”
Section: Discussionsupporting
confidence: 70%
“…22 Two to 4 days after birth, the smooth muscle cells are myoblasts, and development is essentially complete at Ϸ28 days. 22 Morphological studies of aortic development 23 have shown that at birth, the aorta is still undergoing structural development, including hypertrophy and hyperplasia. 23 This also includes a doubling in vessel wall thickness produced primarily by the growth of the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Rat portal venous smooth muscle differentiation occurs within the first 3 wk of the neonatal period, and by 5 wk of age the rat PV displays characteristic phasic contractile activity (116,217). In species that are more mature at birth such as cat, guinea pig, and human this process may begin prenatally but extends well into the postnatal period (31,134).…”
Section: Blood Vessel Developmentmentioning
confidence: 99%